Antioxidative Polyphenols from Defatted Oilseed Cakes: Effect of Solvents - Sue-Siang Teh; Alaa El-Din Bekhit; John Birch (MDPI AG, 2014)
Defatted hemp, flax and canola seed cakes were extracted with different solvent systems namely methanol, ethanol, acetone, methanol 80%, acetone 80% and mixed solvent of methanol:acetone:water (MAW, 7:7:6, v/v/v). Each extract was analyzed for antioxidant capacity using ferric reducing/antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays. MAW exhibited the highest extraction of phenolic and flavonoid contents in the seed cakes, followed by acetone 80% and methanol 80%. The antioxidant capacity was proportional to the polyphenols recovery in the extracts. Canola seed cakes possessed the highest recovery of polyphenols and antioxidant capacity, followed by hemp and flax seed cakes. MAW extract of canola contained total phenolic content, 2104.67 ± 2.52 mg GAE/100 g fresh weight; total flavonoids, 37.79 ± 0.04 mg LUE/100 g fresh weight; percentage inhibition of DPPH•, 33.03 ± 0.38%; FRAP assay, 8.78 ± 0.07 μmol Fe (II)/g fresh weight. Identification of individual polyphenol compounds were performed HPLC. MAW extract of canola had the highest (P < 0.05) concentration of all individual polyphenols except gallic acid and catechin. Highest concentration of quercetin and luteolin in MAW extract of hemp was obtained among all solvent systems.